The Blue Survey: Validation of an instrument to measure ocean literacy among adults - PAREDES-CORAL, EVELYN; DEPREZ, TIM; MOKOS, MELITA; VANREUSEL, ANN; ROOSE, HENK (Mediterranean Marine Science, 2022)
Human activities have put the ocean under unprecedented pressure. Still, levels of public understanding about the ocean remain low. Ocean literacy is a global movement that aims to improve the understanding of the ocean and provide an incentive for positive change in people’s behavior. To date, there is no validated scale targeted to adults to measure ocean literacy that includes measuring people’s knowledge about the ocean, as well as surveying their attitudes and willingness to act. The Blue Survey is an online instrument meant to measure ocean literacy in adult populations developed by a multidisciplinary team of experts. Using factor analysis, we explore the validity and internal consistency of the Blue Survey in a purposive online sample of 251 adults. We found ocean literacy to consist of six sub-dimensions captured by 34 survey items, viz. knowledge of ocean-related topics, personal interest in ocean-related aspects, ocean stewardship, ocean as an economic resource, ocean-friendly behavior, and willingness to act responsibly for the ocean. Our analysis resulted in the development of a new validated instrument to measure the various dimensions of ocean literacy. It may help researchers and practitioners to better understand the factors contributing to shaping an ocean-literate person. Further research should assess the validity of the Blue Survey across different populations, including those closely related to the sea, such as maritime professionals.